x =first number
x+1 = second number
(x) + 4 = x + 4 = 1 ^ new number [first number + 4]
(x + 1) -2 = x - 1 = 2 ^ new number [second number - 2]
![(x+4)/(x-1)=(11)/(16)](https://img.qammunity.org/2021/formulas/mathematics/high-school/dpxx6e4r31kil2tavfvltfcydbw9yhdx7t.png)
now, we resolve it:
![(16(x+4)-11(x-1))/(16(x-1))=0](https://img.qammunity.org/2021/formulas/mathematics/high-school/vn6wpkadxmqi96qixflyht515rkvs1h90i.png)
![(16x+64-11x+11)/(16x-16)=0](https://img.qammunity.org/2021/formulas/mathematics/high-school/z1trs1d553wxzhv2piw8pojqsycsa3sqbn.png)
![(5x+75)/(16x-16)=0](https://img.qammunity.org/2021/formulas/mathematics/high-school/l5qmrdxh87t3p0s2ws6f4skbcke8000e7v.png)
we eliminate the denominator and do c.e.: 16x - 16 ≠ 0; 16x ≠ 16; x ≠ 1
5x + 75 = 0
x = - 15
so x + 1 = - 14
But what you ask are two positive numbers! Are you sure that you write correctly the question? Thank you